The Relationship Between Suicidal Ideation and Parental Attachment Among Adolescents: The Mediator of Anhedonia and Peer Attachment - Guo, Yaru; Ji, Yifu; Huang, Yunheng; Jin, Man; Lin, Yanting; Chen, Yun; Zhang, Lei; Zhu, Chunyan; Yu, Fengqiong; Wang, Kai (Frontiers in Psychology, 2021)
Background: Previous studies had shown that poor quality of early parental attachment is a risk factor for suicide, but few have focus on the mechanism between suicidal ideation and parental attachment. The aim of this study was to explore how parental attachment, anhedonia, and peer attachment were associated with suicidal ideation in adolescents. Method: Participants were enrolled in middle schools, in Hefei, Anhui, China. All participants completed socio-demographic characteristic and standard assessments on parental attachment, peer attachment, anhedonia, and suicidal ideation by paper surveys. The effect of parental attachment on suicidal ideation mediated by anhedonia and peer attachment was analyzed by a structural equation model (SEM) using SPSS AMOS 23.0. Results: The SEM analysis revealed that the standard total effect of parental attachment on suicidal ideation was −0.137 (Z = −27.00, 95% confidence interval [CI; −0.147, −0.127], P < 0.001), with a direct effect of parental attachment on suicidal ideation of −0.107 (Z = −21.40, 95% CI [−0.117, −0.098], P < 0.001), while the indirect effects were −0.002 (Z = −3.33, 95% CI [−0.003, −0.002], P < 0.001) in the pathway of parental attachment-anhedonia-peer attachment-suicidal ideation, −0.019 (Z = −19.00, 95%CI [−0.022, −0.017], P < 0.001) in the pathway of parental attachment- anhedonia-suicidal ideation, and −0.008 (Z = −7.00, 95% CI [−0.010, −0.007], P < 0.001) in the pathway of parental attachment-peer attachment-suicidal ideation. Conclusions: The study suggested that parental attachment could directly influence suicidal ideation and indirectly influence suicidal ideation via anhedonia and peer attachment. The results emphasized the importance of attachment in infancy, and verified the feasibility of intervention on anhedonia and peer attachment to prevent suicidal ideation.